DESAIN SISTEM KENDALI UMPAN BALIK STATE PADA KASUS KONTINYU UNTUK MEJA KERJA CNC - Mangkusasmito, Fakhruddin; Nugroho, Tsani Hendro (Vocational School Diponegoro University, 2019)
Fakhruddin Mangkusasmito, Tsani Hendro Nugroho in this paper explain that One of the important control system in the manufacturing industry is the position control. Mainly in the Computer Numerical Control (CNC) machine, work-table motion control system is used to regulate work-table movements when the machine process a workpieces on it. On standard machines, work-table movements are two axes (X-Y), which is driven by a motor and lead-screw. The discussion in this research only focus on one axis assuming that the systems on both axes are the same and independent. In this research, MATLAB is used to describe the behaviour of the system and also to design appropriate control system in continuos system using state feedback linear controller such as pole placement , tracking system, full order compensator and reduced order compensator. The goal is to obtain a fast response with a rapid rise time and settling time to a step command, while not exceeding an overshoot of 5%. The specification are than a percent overshoot equal to1%, 0,05s settling time and 0,03s rise time. The performance of each control methods are simulated and analyzed to decide the best suit control method for the systems with such criteria. And the result verify that using tracking system controller method achieve such specification with 0% overshoot, 0,04s settling time and 0,028s rise time.